1998
DOI: 10.1074/jbc.273.32.20354
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-mediated Induction of Ceramide Production Is Redox-sensitive

Abstract: The present study underlines the importance of reactive oxygen species in cytokine-mediated degradation of sphingomyelin (SM) to ceramide. Treatment of rat primary astrocytes with tumor necrosis factor-␣ (TNF-␣) or interleukin-1␤ led to marked alteration in cellular redox (decrease in intracellular GSH) and rapid degradation of SM to ceramide. Interestingly, pretreatment of astrocytes with N-acetylcysteine (NAC), an antioxidant and efficient thiol source for glutathione, prevented cytokine-induced decrease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(72 citation statements)
references
References 49 publications
7
64
1
Order By: Relevance
“…To examine the role of ceramide generation in iNOS expression, we utilized the antioxidant PDTC, which has been shown to inhibit ceramide generation in C6 cells induced by TNF-␣ (22). In agreement with previous results (32), PDTC completely blocked iNOS expression induced by TNF-␣.…”
Section: Tnf-␣ Regulates Inos and Gtpch Expression By Distinctsupporting
confidence: 69%
See 2 more Smart Citations
“…To examine the role of ceramide generation in iNOS expression, we utilized the antioxidant PDTC, which has been shown to inhibit ceramide generation in C6 cells induced by TNF-␣ (22). In agreement with previous results (32), PDTC completely blocked iNOS expression induced by TNF-␣.…”
Section: Tnf-␣ Regulates Inos and Gtpch Expression By Distinctsupporting
confidence: 69%
“…To study the potential role of ceramide in cytokine-stimulated BH 4 production, we used C6 rat astroglioma cells, a convenient model astrocyte cell line. Furthermore, in this cell line, as in primary astrocytes, TNF-␣ has been shown to stimulate degradation of sphingomyelin to ceramide (22). Although ceramide generation, similar to TNF-␣ treatment potentiated NO and iNOS expression induced by IFN-␥ plus IL-1␤, surprisingly, we found that it did not mimic the effects of TNF-␣ on BH 4 or GTPCH expression.…”
contrasting
confidence: 47%
See 1 more Smart Citation
“…TNF-α-stimulated cells are redox-sensitive [28]. Some studies showed that ROS participate in TNF-α-mediated ceramide formation, suggesting that the ROS-sensitive pathway may be located upstream of ceramide formation [29]. While other studies demonstrated that ceramide plays a role as an intermediate in TNF-α-mediated ROS production [30].…”
Section: Tumor Necrosis Factor-α and Ceramidementioning
confidence: 99%
“…Thus, HIV-infected macrophages may be rendered incapable of producing excessive cysteine because of oxidative stress and subsequent glutathione depletion. In fact, this cytokine-mediated induction of ceramide and glutathione depletion is redox sensitive, and therefore can be reversed with cysteine derivatives (55).…”
Section: Discussionmentioning
confidence: 99%